(untitled) (Conference Zone, 2022)
Teaching students to listen is challenging yet rewarding skill that all teachers need to know. Listening and retaining information are two of the most important facets of teaching. Learning tips and tricks for the classroom for the applicable age and grade level are vital for a successful teaching experience. Teachers learn a wealth of ideas from other teachers. Experiences, strengths and background knowledge from fellow teachers are all effective in sharing techniques that work.